Penerapan Metode Pemecahan Masalah terhadap Konsepsi Siswa Ditinjau dari Gaya Kognitif Siswa Sekolah Dasar - Yuliana Yuliana; Edy Waluyo; Muhammad Halqi (Journal of Elementary School (JOES), 2021)
The purpose of this study was to determine the differences in students' conceptions between those taught by problem solving and conventional methods, in students who have field independent (FI) and field dependent (FD) learning styles. good when viewed from the cognitive style of students. The type of research that will be conducted in this research is quantitative research with experimental model. The population in this study were all students of the 8 Pringgabaya State Elementary School in the 2020/2021 academic year, and the sample consisted of 2 classes, namely: Class V (20 students) and VI (21 students). Data collection techniques used are documentation techniques, questionnaire techniques and test techniques. The conclusions in this study include: (1) There is an influence between students' conceptions of the learning methods given during learning. The concept of Field Independent students with the Problem solving learning method is better than the conception of Field Dependent students with the Conventional Learning method; (2) The conception of students with Fiel Independent cognitive style has a greater mean (average) when compared to the conception of students with Fiel Dependent cognitive style, in other words the conception of students with Fiel Independent cognitive style is better when compared to the conception of students with Fiel Dependent ; (3)Students' conceptions with problem solving methods have better conceptions when compared to students' conceptions with conventional learning methods; (4) There are conceptual differences between students who have Field Independent cognitive style when given treatment with problem solving learning and conventional learning methods; (5) There is a difference in conception between students who have a Field Dependent cognitive style when given treatment with problem solving learning and there is no difference in conception when students are treated with conventional methods; (6) There are differences in students' conceptions between those who have Field Independent and Field Dependent cognitive styles when given learning treatment with problem solving methods; (7) There are differences in students' conceptions between those who have Field Independent and Field Dependent cognitive styles when given learning treatment with Conventional Methods. Keywords: Problem Solving, Conception, Cognitive Style